2012
DOI: 10.1111/j.1863-2378.2012.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Hepatitis E Virus in Domestic Pigs of Different Ages in Portugal

Abstract: This study represents the primary hepatitis E virus (HEV) surveillance in domestic pigs in Portugal, five pig farms were investigated in 5 different Portuguese regions, ten faecal samples were collected at four different stages of the production. All faecal samples were tested for hepatitis E virus by real-time RT-PCR. At least one sample from each farms of all age groups tested positive for HEV. The prevalence in the pig herds varied from 10% to 30% and the mean prevalence was 32% in weaners, 20% in growers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…HEV is generally transmitted through a fecal-oral route (Worm et al, 2002;Hsieh et al, 1999). According to seroprevalence surveys, the numbers of unrecognized or subclinical infections are under-estimated in many countries (Ijaz et al, 2005;Xiao et al, 2012;Berto et al, 2012;Hakze-van der Honing et al, 2011). Because anti-HEV antibodies have been detected in wild and domestic rats, rodents are considered a potential reservoir of HEV (Kabrane-Lazizi et al, 1999;Huang et al, 2009;Maneerat et al, 1996).…”
Section: Q4mentioning
confidence: 99%
“…HEV is generally transmitted through a fecal-oral route (Worm et al, 2002;Hsieh et al, 1999). According to seroprevalence surveys, the numbers of unrecognized or subclinical infections are under-estimated in many countries (Ijaz et al, 2005;Xiao et al, 2012;Berto et al, 2012;Hakze-van der Honing et al, 2011). Because anti-HEV antibodies have been detected in wild and domestic rats, rodents are considered a potential reservoir of HEV (Kabrane-Lazizi et al, 1999;Huang et al, 2009;Maneerat et al, 1996).…”
Section: Q4mentioning
confidence: 99%
“…These studies showed that the prevalence of HEV RNA in swine faeces and serum depend on the production stage, i.e. the pig’s age (Additional file 2 [14, 15, 18, 21, 57, 66, 86–89, 9193, 95, 96, 104, 108, 109, 113, 114, 118–120, 133, 135, 136, 140–150]). A broad shedding period from 1.5 to 5 months of age was globally reported at farm scale.…”
Section: Hev Infection Characteristics and Dynamics On Pig Farmsmentioning
confidence: 99%
“…To the Editor: Hepatitis E virus (HEV; family Hepeviridae , genus Hepevirus ) is a positive-stranded RNA virus with a genome of ≈7.2 kb that contains 3 open reading frames ( 1 , 2 ). On the basis of sequence analysis, mammalian HEVs are classified into 4 recognized genotypes ( 3 , 4 ).…”
mentioning
confidence: 99%